Modelling headloss and two-step denitrification in a full-scale wastewater post-denitrifying biofiltration plant. Issue 3 (1st March 2014) - Bernier, Jean; Lessard, Paul; Rocher, Vincent
Abstract : The NO3 − /NO2 − removal and headloss evolution behaviour of a post-denitrification wastewater biofiltration stage using methanol as an external carbon source was modelled. Three datasets collected on different time scales and at different locations on a full-size plant from the Paris conurbation (800  000 population equivalent) were used in this study. The model was first calibrated on a short-term experiment, during which a shift in the methanol to NOX ratio was imposed at the influent of a treatment lane. Measurements were taken at different frequencies at the effluent as well as at different heights inside the media bed. The model was then used on a 240-day period in 2008 to simulate the behaviour of the whole denitrification stage. Results were good overall for most simulated variables, although nitrite was overestimated for the long-term dataset. Results showed that the model is highly sensitive to variations on the amounts of methanol injected during treatment, especially regarding nitrite and headloss.